The Effect Of Product Packaging Quality And Price On Consumer Buying Interest In Tempe Chips In Talang Way Sulan Village, way sulan district, South Lampung Regency - Heni Yurika; Agus Purnomo (Cita konsultindo, 2025)
The snack food sector is currently growing rapidly driven by increasing customer demand for local products. However, in the snack food market, competition is getting tighter, especially since similar products from various regions offer variations in taste, quality and price. In the field, there are problems related to consumer interest in buying local tempeh chips. Although this product has great potential, many business actors have not managed the quality of packaging and pricing optimally. Several tempeh chip producers in Talang Way Sulan Village use packaging that is less attractive and not durable, so that the product becomes easily damaged and less desirable by consumers. This study purpose for test effect at product packaging quality by price at constumer pickup importance at tempeh chips in Talang Way Sulan Village, Way Sulan District, South Lampung Regency. The outcome of the study show lest the quality of product packaging have a significant effect in constumer purchasing importane, with a significance level of <0.05. Likewise, price, which even have a significant effect in constumer pick up importane. Simultaneously, these two variables have significant effect in constumer pick up importane in tempeh chips in the village. This finding provides an important contribution for business actors in improving the quality of packaging and pricing to attract consumer purchasing interest.